Electrodeposition of Ni-B and Ni-Co-B Alloys by Using Boric Acid as Boron Source - Sakita, A. M. P. [UNESP]; Della Noce, R. [UNESP]; Magnani, M. [UNESP]; Fugivara, Cecilio Sadao [UNESP]; Benedetti, Assis Vicente [UNESP] (Electrochemical Soc Inc, 2014)
In this letter, the formation of electrodeposited Ni-B and Ni-Co-B alloys by using boric acid as boron source was demonstrated. The estimated thickness of the films was 5 mu m. By means of Cyclic voltammetry, X-ray diffractometry and energy dispersive X-ray spectroscopy analyzes, it was showed that Ni-B and Ni-Co-B alloys, with composition Ni94B6 and Ni75Co21B4, can be easily formed onto glassy carbon when no complexing agents are employed in the electrodeposition bath. These results open the door to the production of electrodeposited boron-containing alloys by using boric acid as precursor due to its low cost and large-scale production. (C) 2014 The Electrochemical Society. All rights reserved.